The Spanish Labor Market: A Gender Approach - Dancausa Millán, Mª Genoveva (Int J Environ Res Public Health, 2021)
The massive incorporation of Spanish women into the labor market is a phenomenon that began in the second half of the 20th century, being many the obstacles that this group has had to overcome to reach the current situation, where getting a job can be an achievement that, in many cases, does not correspond to the capacity and academic training of the worker, creating a labor and economic imbalance (the cost in training is not rewarded with the work done). In this work, the Spanish labor market was analyzed through the labor force survey (EPA) from a gender perspective, demonstrating the existing inequalities at the labor level, both of employment and unemployment rates, and of jobs where the glass ceiling is evident and of economic remuneration where the salary gap continues to be important. In addition, through an ARIMA model, the evolution of the number of Spanish working women was analyzed, and how the economic crisis of 2009 and the sanitaria have affected their employment in the various crises (COVID-19). Measures to solve the problem as well as laws and active policies in favor of the creation of female jobs and a greater awareness of empowerment on the part of the female collective are proposed.